THE PRACTICE OF PAGANG GADAI OF HIGH HERITAGE ASSETS IN KANAGARIAN GANGGO MUDIAK IN THE PERSPECTIVE OF ISLAMIC LAW - Al Ikhlas, Al Ikhlas; Murniyetti, Murniyetti; Engkizar, Engkizar (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to analyze how the practice of pagang gadai is carried out by the community according to the perspective of Islamic law. This study uses a qualitative method with a phenomenological approach, data sources are taken through interviews with ten people in Kenagarian Ganggo Mudiak, Pasaman Regency, West Sumatra Province. To strengthen the interview data, the researcher also made direct observations on the process and procedures for the practice pagang gadai is carried out by the community at the research location. All research data were then analyzed using the Miles & Huberman technique. The research findings found two community mistakes in the practice of pagang gadai, namely i) pagang gadai is carried out by the community in Kanagarian Ganggo Mudiak is not in accordance with gadai in the perspective of Islamic sharia law, ii) the practice of pagang gadai is carried out by the community contains elements of usury which is legally contrary to sharia. Islam. Whereas in the Islamic context the application of gadai is not for profit but aims to help others. The recommendation from the research findings is that it is necessary to provide education to the public about how to pagang gadai procedures that are in accordance with Islamic sharia guidelines so that the error in practices is pagang gadai is not sustainable in the community